2009
DOI: 10.1042/bj20081874
|View full text |Cite
|
Sign up to set email alerts
|

Antizyme 3 inhibits polyamine uptake and ornithine decarboxylase (ODC) activity, but does not stimulate ODC degradation

Abstract: Azs (antizymes) are small polyamine-induced proteins that function as feedback regulators of cellular polyamine homoeostasis. They bind to transient ODC (ornithine decarboxylase) monomeric subunits, resulting in inhibition of ODC activity and targeting ODC to ubiquitin-independent proteasomal degradation. Az3 is a mammalian Az isoform expressed exclusively in testicular germ cells and therefore considered as a potential regulator of polyamines during spermatogenesis. We show here that, unlike Az1 and Az2, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…The modulations of the proteasome-interacting surface explain why the alternative heterodimers cannot be recognized by the proteasome, consistent with the roles of Az 2 and Az 3 as simple catalytic inhibitors of ODC (21,25).…”
Section: Az 1 Binding Primes Odc For Ubiquitin-independent Proteasomementioning
confidence: 87%
“…The modulations of the proteasome-interacting surface explain why the alternative heterodimers cannot be recognized by the proteasome, consistent with the roles of Az 2 and Az 3 as simple catalytic inhibitors of ODC (21,25).…”
Section: Az 1 Binding Primes Odc For Ubiquitin-independent Proteasomementioning
confidence: 87%
“…HEK-293 cells were transfected using the calcium phosphate method (28). NIH3T3 cells expressing the tetracycline-responsive repressor were grown and stimulated for the expression of Az as described (29).…”
Section: Methodsmentioning
confidence: 99%
“…The ability of Az2 to stimulate protein degradation was tested only in cells, as it was demonstrated previously that Az2 does not stimulate ODC degradation in an in vitro degradation reaction (29,35). Simultaneous cotransfection of Az with all four tested proteins demonstrated that, like Az1, Az2 did not stimulate the degradation of cyclin D1, Aurora-A, and ⌬Np73 but efficiently stimulated ODC degradation (Fig.…”
Section: Inducible Az1 Expression Inhibits Proliferation Of Nih3t3 Cementioning
confidence: 99%
“…[35][36][37] AZ3 maintains polyamine homeostasis during spermatogenesis but does not mediate ODC degradation. [32,38] It was found that AZ3 transcription was restricted to testis germ cells, starting early in spermiogenesis and finishing in the late spermatid phase. [10] Since the AZ3 wave of expression follows the wave of high ODC expression that takes place during the early phases of spermatogenesis, it was postulated that the physiological role of AZ3 was to abolish ODC activity to avoid the detrimental effects of putrescine during spermiogenesis.…”
Section: Discussionmentioning
confidence: 99%